2005
DOI: 10.1073/pnas.0408864102
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase mutations identified in human cancer are oncogenic

Abstract: Akt ͉ oncogenic transformation ͉ p110␣ ͉ PIK3CA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
632
4
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(672 citation statements)
references
References 44 publications
25
632
4
11
Order By: Relevance
“…Transformation by constitutively active chicken p110a and cancer-specific mutants of p110a has been shown to involve TOR and its downstream targets, ribosomal protein S6 kinase 70 kDa polypeptide 1 (S6K) and eukaryotic initiation factor 4E binding protein (4E-BP1) (Aoki et al, 2001;Kang et al, 2005). Degradation of FoxO1 also occurs during transformation induced by the oncogenic myristylated chicken p110a (Aoki et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation by constitutively active chicken p110a and cancer-specific mutants of p110a has been shown to involve TOR and its downstream targets, ribosomal protein S6 kinase 70 kDa polypeptide 1 (S6K) and eukaryotic initiation factor 4E binding protein (4E-BP1) (Aoki et al, 2001;Kang et al, 2005). Degradation of FoxO1 also occurs during transformation induced by the oncogenic myristylated chicken p110a (Aoki et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The specific functions of the non-a class I PI3K isoforms in normal physiology suggested that the mechanism of transformation induced by these oncoproteins could be different. Oncogenic signaling of p110d and of cancer-specific mutants p110a is correlated with constitutive activation of Akt (Kang et al, 2005). However, the p110g isoform activates Akt only conditionally, whereas p110b does not mediate detectable phosphorylation of Akt (Zhao et al, 2005;Kang et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…19,33 Activated PI3-kinase phosphorylates inositol lipids, resulting in the activation of the serine/threonine kinase PKB that phosphorylates caspase-9 and BAD, promoting cell survival. 19 Activated PKB can also regulate cellular proliferation by interaction in the nucleus with cell cycle regulators governing G1/S and G2/M checkpoints.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA somatic mutations are frequently associated with a variety of solid tumors including breast, colon, lung, ovarian, and gastric cancer 15, 16, 17 and they are also observed in patients with overgrowth syndromes, categorized as PROS 18. Somatic mosaic PIK3CA mutations can affect different tissues.…”
Section: Discussionmentioning
confidence: 99%